Aging impairs deliberation and behavioral flexibility in inter-temporal choice - Breton, Yannick-André; Seeland, Kelsey D.; Redish, A. David (Frontiers in Aging Neuroscience, 2015)
Inter-temporal choice depends on multiple, interacting systems, some of which may be compromised with age. Some of these systems may be responsible for ongoing trial-by-trial choice strategies. Some may represent the consequences of action. Some may be necessary for the coupling between anticipated consequences and strategies currently in use, flexibly guiding behavior. When faced with a difficult decision, rats will orient back and forth, a behavior termed ``vicarious trial and error'' (VTE). Recent experiments have linked the occurrence of VTE to hippocampal search processes and behavioral flexibility. We tested 5 month (n=6), 9 month (n=8) and over-27 month-old (n=10) rats on a Spatial Adjusting Delay Discounting task to examine how aging impacted lap-by-lap strategies and VTE during inter-temporal choice. Rats chose between spatially separated food goals that provided a smaller-sooner or larger-later reward. On each lap, the delay to the larger-later reward was adjusted as a function of the rat's decisions, increasing by 1 second after delayed-side choices and decreasing by 1 second after non-delayed side choices. The strategies that aged rats used differed from those used in young and adult rats. Moreover, aged rats produced reliably more VTE behaviors, for protracted periods of time, uncoupled from behavioral flexibility.